PyXPCSviewer: an open‐source interactive tool for X‐ray photon correlation spectroscopy visualization and analysis. (7th June 2022) - Chu, Miaoqi; Li, Jeffrey; Zhang, Qingteng; Jiang, Zhang; Dufresne, Eric M.; Sandy, Alec; Narayanan, Suresh; Schwarz, Nicholas
Abstract : The Python‐based graphical user interface pyXPCSviewer that is deployed at beamline 8‐ID‐I of the Advanced Photon Source for interactive visualization of X‐ray photon correlation spectroscopy results is introduced. Abstract : pyXPCSviewer, a Python‐based graphical user interface that is deployed at beamline 8‐ID‐I of the Advanced Photon Source for interactive visualization of XPCS results, is introduced. pyXPCSviewer parses rich X‐ray photon correlation spectroscopy (XPCS) results into independent PyQt widgets that are both interactive and easy to maintain. pyXPCSviewer is open‐source and is open to customization by the XPCS community for ingestion of diversified data structures and inclusion of novel XPCS techniques, both of which are growing demands particularly with the dawn of near‐diffraction‐limited synchrotron sources and their dedicated XPCS beamlines.